Peran Dalam Memotivasi Belajar Membaca Siswa Kelas Satu Sekolah Dasar: Persepsi Guru - Annisa, Iffat Tia; Danang Dwi Basuki; Fitri Yessi Jami (STAI AL-AMIN, 2024)
Reading learning is one of the lessons that has an important role in the learning process. Reading is one of the main foundations in developing knowledge. The way to foster interest in learning to read in students is by motivation from a teacher. In this study, researchers used descriptive qualitative methods. The data in this study were obtained through interviews, observation and documentation. The results of this study can be concluded that the role of teachers in motivating learning to read to first grade elementary school students is needed. Various ways of motivation that can be done by the teacher. Each teacher has different ways of providing motivation. It can be seen that in every activity created by the teacher in the process of providing motivation to students. students look happy and enthusiastic in learning to read.